La corriente ortodoxa dentro del judaísmo estadounidense: evolución y distanciamiento - Álvarez, Ana (UNISCI Discussion Papers, 2007)
The perception of the U.S. Jewish community from the outside is that of an homogeneous and solid block, capable of articulating a common position and defining shared interests. This article aims to show the increasing division between the majority Jewish sectors, always identified with liberalism and the Democratic Party, and the minority orthodox sector that, although it has bever shared the majority’s positions, has never made these differences public until recently. The U.S. orthodox Jews are analyzed from a demographic, sociological, theological and political standpoint, their likely evolution in the middle and long term, and how their entrance into the public arena could affect the interests of the U.S. Jewish community as a whole.